Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1029/2004gl020089
|View full text |Cite
|
Sign up to set email alerts
|

Carbon kinetic isotope effects in the gas‐phase reactions of aromatic hydrocarbons with the OH radical at 296 ± 4 K

Abstract: The carbon kinetic isotope effects (KIEs) of the room temperature reactions of benzene and several light alkyl benzenes with OH radicals were studied in a reaction chamber at ambient pressure using gas chromatography coupled with online combustion and isotope ratio mass spectrometry (GCC‐IRMS). The KIEs are reported in per mil according to ɛ (‰) = (KIE − 1) × 1000, where KIE = k12/k13. The following average KIEs were obtained, (all in ‰): benzene 7.53 ± 0.50; toluene 5.95 ± 0.28; ethylbenzene 4.34 ± 0.28; o‐xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 15 publications
4
69
0
Order By: Relevance
“…The gas chromatography combustion isotope ratio mass spectrometry (GCC-IRMS) technique used in this investigation is very similar to those described previously for the measurements of stable carbon isotope KIE values (Anderson et al, 2004a(Anderson et al, ,b, 2007aIannone et al, 2003Iannone et al, , 2008. KIE experiments are similar in concept to relative rate (RR) experiments.…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…The gas chromatography combustion isotope ratio mass spectrometry (GCC-IRMS) technique used in this investigation is very similar to those described previously for the measurements of stable carbon isotope KIE values (Anderson et al, 2004a(Anderson et al, ,b, 2007aIannone et al, 2003Iannone et al, , 2008. KIE experiments are similar in concept to relative rate (RR) experiments.…”
Section: Methodssupporting
confidence: 55%
“…n-alkanes + OH, alkenes + O 3 , etc. ), KIE values were fitted as a function of the inverse carbon number, N C -1 Iannone et al, 2003Iannone et al, , 2008Anderson et al, 2004aAnderson et al, ,b, 2007a. As can be seen from Figure To date, there are no previously published KIE values for the reactions of MVK and MACR with OH radicals.…”
Section: Comparison With Previously Published Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As the reaction progresses, the products will be enriched in 13 C due to the reaction of the parent VOC as well as that of the reaction product with the OH radical in the gas phase. Although the KIEs for reactions of nitrophenols have not been measured, they most likely will be normal KIEs, similar to all KIEs measured for reactions of light aromatic VOCs in the gas phase (Anderson et al, 2004). The overview of the results in Figs.…”
Section: Overview Of Measured Carbon Isotope Ratiosmentioning
confidence: 99%
“…Irei et al (2015) reported that the main factor determining the carbon isotope ratio of the particulate phase products of toluene oxidation is the kinetic isotope effect (KIE) for the reaction of toluene with the OH radical and the carbon isotope ratio of the reacting toluene. The KIEs for the reactions of benzene, toluene and m-xylene with the OH radical have been measured in the laboratory (Anderson et al, 2004) and the carbon isotope ratio of their emissions in the Greater Toronto Area (GTA) have been determined by Rudolph et al (2002). Using these values, which are summarized in Ta- Table 3.…”
Section: Overview Of Measured Carbon Isotope Ratiosmentioning
confidence: 99%